DAILY MEMORY LAPSES AND PSYCHOLOGICAL WELL-BEING. (11th November 2018) - Mogle, J; Hill, N; Almeida, D
Abstract: People who report more memory lapses also tend to have higher negative and lower positive affect, on average. However, it is less clear what happens on days when an individual experiences a memory lapse on in everyday life. Adults (n=780, Mage=48, range 25–75, 55% female) completed daily diaries on 8 consecutive nights. Each night participants reported memory lapses (prospective and retrospective) as well as positive and negative affect. Using multilevel modeling, we found on days when an individual reported any memory lapse they reported significantly higher negative affect (retrospective: b=.026, SE=.009, p<.01; prospective: b=.033, SE=.009, p<.01) compared to days without a lapse. Prospective memory lapses were related to lower positive affect (b=-.04, SE=.015, p=.01), whereas retrospective memory lapses were related to lower positive affect but only in younger adults (p<.01). The importance of treating daily memory lapses as an unmeasured form of stressful event will be discussed.